Effects of Physical Activity, Exercise and Sport on Executive Function in Young People with Attention Deficit Hyperactivity Disorder: A Systematic Review - Felipe Montalva-Valenzuela; Oscar Andrades-Ramírez; Antonio Castillo-Paredes (European Journal of Investigation in Health, Psychology and Education, 2022)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder that negatively affects the inattention, disorganization, and/or hyperactivity–impulsivity in children and adolescents who suffer from it, included cases being reported that continue into adulthood. This disorder impairs social, academic, emotional, psychological, and health system functioning due to its high cost of treatment. The present systematic review aims to analyze the effects of physical activity, exercise, and sports on the executive function in children and adolescents diagnosed with ADHD through the scientific literature. The results show that the practice of physical activity, exercise, or sport produces improvements in executive function in children and adolescents diagnosed with ADHD, mainly through aerobic exercise. A 20 min session of physical activity, sport, or exercise leads to improvements in executive functions in children and adolescents with ADHD. It can be concluded that the practice of physical activity, exercise, and sport generate improvements on executive functions in children and adolescents with ADHD, mainly through aerobic exercise.